KCNMA1 cooperating with PTK2 is a novel tumor suppressor in gastric cancer and is associated with disease outcome - Ma, Gaoxiang (Mol Cancer, 2017)
BACKGROUND: Inactivation of tumor suppressor genes by promoter hypermethylation plays a key role in the tumorgenesis. It is necessary to uncover the detailed pattern of whole genome-wide abnormal DNA methylation during the development of gastric cancer (GC). METHOD: We performed a genome-wide methylation detection using 12 paired of GC tissues and their corresponding normal tissues. Methylation-specific PCR (MSP) and bisulphite sequencing (BSP) were used to measure methylation status of specific CpG site. Based on the bioinformatic analysis, the cell phenotypes and mouse model experiments were constructed to detect effect of the target gene. Using the Kaplan–Meier survival curve, the clinical value of KCNMA1 was assessed in GC patients. RESULTS: The CpG site cg24113782 located at the promoter of KCNMA1 showed the most significant difference, contributing to the commonly silenced KCNMA1in gastric cancer cells and primary GC tissues. The promoter methylation of KCNMA1 was detected in 68.7% (77/112) of tumor tissues, compared with 16.2% (18/112) of normal tissues (P < 0.001). The survival curve indicated that KCNMA1 hypermethylation was significantly associated with the shortened survival in GC patients (P = 0.036). KCNMA1 significantly inhibited biological malignant behavior of gastric cancer cell by inducing cell apoptosis in vitro, and suppressed xenograft tumor growth in subcutaneous mouse models (both P < 0.001). Furthermore, the anti-tumor effect of KCNMA1was mediated through suppressing the expression of PTK2. CONCLUSION: KCNMA1 is a critical tumor suppressor in gastric carcinogenesis and its hypermethylation is an independent prognostic factor in patients with gastric cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12943-017-0613-z) contains supplementary material, which is available to authorized users.